Development of Mathematical Literacy Tests to Measure Student’s Reasoning and Representation Skills - Sari, Novita; Sukmaningthias, Novika; Nuraeni, Zuli; Rosyada, Amrina (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini bertujuan untuk menghasilkan tes literasi matematika untuk mengukur penalaran dan representasi matematis siswa pada materi SPLDV yang valid dan memiliki karakteristik yang baik. Penelitian ini mengadopsi prosedur pengembangan R&D, yakni pengumpulan informasi, pengembangan produk, dan uji coba & revisi awal. Instrumen yang digunakan berupa lembar validasi. Analisis data menggunakan Microsoft Excel dan SPSS 26. Hasil penelitian menunjukkan bahwa, melalui validasi ahli, instrumen tes yang dikembangkan dapat digunakan untuk mengukur penalaran dan representasi matematis siswa dan butir soal terkategori valid, reliabel, tingkat kesukaran sedang dan tinggi, serta daya pembedanya baik. This study aims to produce a mathematical literacy test to measure students' mathematical reasoning and representation on system of linear equations in two variables (SLETV) material that is valid and has good characteristics. This research adopts R&D development procedures, namely information gathering, product development, and initial trials & revisions. The instrument used was a validation sheet. Data analysis using Microsoft Excel and SPSS 26. The results of the study showed that, through expert validation, the developed test instrument can be used to measure students' mathematical reasoning and representation and the test items are categorized as valid, reliable, moderate and high levels of difficulty, and have good discriminatory power.